2018
DOI: 10.1111/tpj.13819
|View full text |Cite
|
Sign up to set email alerts
|

The major‐effect quantitative trait locus CsARN6.1 encodes an AAA ATPase domain‐containing protein that is associated with waterlogging stress tolerance by promoting adventitious root formation

Abstract: In plants, the formation of hypocotyl-derived adventitious roots (ARs) is an important morphological acclimation to waterlogging stress; however, its genetic basis remains fragmentary. Here, through combined use of bulked segregant analysis-based whole-genome sequencing, SNP haplotyping and fine genetic mapping, we identified a candidate gene for a major-effect QTL, ARN6.1, that was responsible for waterlogging tolerance due to increased AR formation in the cucumber line Zaoer-N. Through multiple lines of evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 81 publications
1
43
0
Order By: Relevance
“…Lal_00049481 AT3G53480 ABCG37 AAA proteins (ATPases Associated with diverse cellular Activities) can be inhibited by EDTA 33 . Members of the G subgroup of the ATP-binding cassette transporter, ABCG36, and its homolog, ABCG37, contain two AAA domains.…”
Section: Chr01mentioning
confidence: 99%
“…Lal_00049481 AT3G53480 ABCG37 AAA proteins (ATPases Associated with diverse cellular Activities) can be inhibited by EDTA 33 . Members of the G subgroup of the ATP-binding cassette transporter, ABCG36, and its homolog, ABCG37, contain two AAA domains.…”
Section: Chr01mentioning
confidence: 99%
“…Transgenic Arabidopsis plants with the cucumber LL gene were developed in both wild-type Col-0 and sod3-1 mutant genetic backgrounds following Xu et al (2018). Briefly, the LL CDS was cloned into the pCAMBIA2301-ky vector carrying the CaMV 35S promoter (CaMV35S:LL).…”
Section: Expression Of Ll Candidate Genes In Arabidopsis and Cucumbermentioning
confidence: 99%
“…After the release of the watermelon genome (Guo et al , ), watermelon has become an ideal model crop for research on traits such as fruit cracking, size, shape, rind colour, and flesh texture due to being an annual and thus having a shorter life cycle than other perennial fruit crops. With the advancement of next‐generation sequencing (NGS) technology, sequencing‐based gene mining strategies, such as bulk segregant analysis (BSA), genetic mapping and genome‐wide association study (GWAS), have been widely used as affordable, efficient and routine approaches to dissect crop traits in rice (Wang et al , ) tomato (Chapman et al , ; Soyk et al , ), cucumber(Li et al , ; Xu et al , ), peanut(Luo et al , ), chickpea(Deokar et al , ),spinach(She et al , ), apple(Jia et al , ) and melon (Hu et al , ). Recently, genes or QTLs related to sugar transporter (Ren et al , ), dwarfism (Dong et al , ) and lobed leaves (Wei et al , ) have been reported in watermelon.…”
Section: Introductionmentioning
confidence: 99%